The Effect of Using Integrated Learning Strategy on the Eight Grade Student's Achievement in Computer Subject in Ajloun Directorate - Ftimat, Jaber Olian Mohammad (Journal of Educational and Psychological Sciences, 2022)
This study aimed to identify the effect of using Integrated learning strategy on the eighth grade student's achievement in Computer subject in Ajloun directorate, the study used the qusai- experimental approach. An achievement test was developed it consist of (30) paragraph and there validity and reliability were confirmed, the sample of study consisted from (53) male student they distributed to control group they were taught in the usual way and experimental group they were taught in the integrated learning strategy way. However, the study showed there was statistical difference at the level (α≤0.05) in the average of the educational achievement test attributed to the teaching strategy, in favor of the member of the experimental group. The study recommended a set of recommendations, the most important of which is the necessity of activating the blended learning strategy in teaching computer subject due to its effectiveness in education.
Keywords: Integrated Learning Strategy; Achievement; computer Subject